The Analysis of Exhaust Gas Characterization in Reducing CO and HC Gas Pollution on the EFI Engine of Daihatsu Luxio 1500 CC - Ismanto Styabudi (LPPM, Institut Teknologi Sepuluh Nopember, Indonesia, 2017)
Air pollution from highways, particularly in an urban area which density and mobility are already on the verge of solid boundaries, resulting in environmental and human health problems. This is due to the lack of standardization of testing exhaust gas by the governmental body. Accurate results from the test and technology standardization on exhaust system which is one important component for gas pollutant elimination from the vehicle. In the present work, we examined the role of some modified exhausts on the level of pollutant exhaust, i.e. CO, HC, NOx gas. Experimental design for controlled variable is the speed, torque of the wheel, and gear position. Several modifications of exhaust gas were tested were tested, i.e. Standard, 3-way catalytic converter, racing and 2-ways catalytic converter. The data is gained through dynamometer and exhaust gas Analyzer as a speedometer gauges, torque wheels, and levels of exhaust gas that comes out of the tailpipe. Statistical analysis of the results uses one-way ANOVA. The result showed that the order in reducing exhaust gas CO and HC are: (1) two-way exhaust gas and 3 Way Catalytic Converter exhaust gas, (2) standard and (3) modified exhausts. 3 Way catalytic converter was the best to eliminate NOx than other three exhaust gas system